Bilateral testicular mass in a 21-year-old male with a history of congenital adrenal hyperplasia: A case report - Amir Reza Abedi; Azade Rakhshan; Mohammad Seifi Poor (Urology Case Reports)
A 21-year-old man was referred because of bilateral testicular swelling from 8 months ago. He had a known history of congenital adrenal hyperplasia (21-hydroxylase deficiency) diagnosed in infancy, managed with glucocorticoid therapy since childhood. However, the patient had been non-adherent to medication for several years. The patient underwent surgery with an inguinal incision, and a biopsy from the mass was sent for frozen section. The frozen and permanent sections were consistent with “Testicular adrenal rest tumor (tumor of adrenogenital syndrome)